PEMETAAN SEBARAN PENYAKIT DI WILAYAH KABUPATEN PROBOLINGGO DENGAN GOOGLE API - Sulistiyanto Sulistiyanto (Jurusan Teknologi Informasi Politeknik Negeri Jember, 2019)
There are three types of disease that generally affects the population Probolinggo district include Dengue Hemorrhagic Fever (DHF), diarrhea and tuberculosis, diseases that often lead to extraordinary events in Indonesia. All three of these diseases can spread rapidly and cause death within a short time. Prediction of the occurrence of Dengue Hemorrhagic Fever (DHF), diarrhea and tuberculosis in Probolinggo need to be made in the form of web-based GIS program. This system helps the government and the public to know the number of patients, in an area, such as an image display data in map form. The research method used is the method of data collection consisted of interviews, observation, and literature. While the development of the system used on the Web GIS uses waterfall method. The design of the map is displayed using the Google Maps API, software used in building this cycle is PHP. Results of this information media creation is